"He Explained It to Me and I Also Did It Myself": How Older Adults Get Support with Their Technology Uses. (December 2019) - Hunsaker, Amanda; Nguyen, Minh Hao; Fuchs, Jaelle; Djukaric, Teodora; Hugentobler, Larissa; Hargittai, Eszter
Given that older adults constitute a highly heterogeneous group that engages with digital media in varying ways, there is likely to be large variation in technology support needs, something heretofore unaddressed in the literature. Drawing on in-depth qualitative interviews with a multinational sample of older adults, the authors explore the support needs of older adults for using digital media, including their perceptions of whether the support they receive meets their needs. Participants obtained assistance from both informal (e.g., adult children) and formal (e.g., computer classes) sources. However, the support given can lack immediacy, leaving older adults dependent on others' availability to provide it. Educational approaches that emphasize individualized support and wide availability might allow an improved experience for a population that is increasingly online with an interest in a wide range of activities.